The possibility of attaining a sustainable future democratic governance in contemporary Nigeria through the instrumentality of social studies education (West African Journal on Sustainable Development, 2024)
This paper examined the possibility of attaining a sustainable future democratic governance in Contemporary Nigeria through the instrumentality of social studies education. Social studies education is seen as a problem-solving course of instruction designed to train and produce effective and active citizens who are fully loaded with critical knowledge, skills, values, and attitudes to enable them to make effective and informed decisions in society. The development of sustainable future democratic governance is at the heart of social studies education as it tries to assist through its teachings to inculcate core social and cultural values in the learners. The paper extensively looked at the concepts and objectives of social studies education, democracy, and democratic governance, and how it can be used to ensure a hitch-free modern Nigerian society.The paper identified government partisanship as one of the main obstacles to the attainment of effective democratic governance in Nigeria, as well as widespread poverty, corruption, political thuggery, ethnic profiling, compromised security personnel, voter suppression, and intimidation, requiring urgent action to reverse this negative trend. Finally, it was noted that a leader’s character, competence, creativity, commitment, thoughtfulness, transparency, and integrity are only a few examples of the elements that solidify sustainable democracy anchored on effective governance.Therefore, the paper recommended among others that, the senior secondary social studies curriculum, as prepared and approved but not yet implemented, must be completely embraced and implemented right away, as this would extend the intellectual agility of the young students and help them fully comprehend the complexity of democratic governance.
Keywords: Social Studies Education; Democracy; Democratic Governance; Development; Contemporary